Altered gut microbiota promotes colitis-associated cancer in IL-1 receptor-associated kinase M-deficient mice - Klimesova, Klara; Kverka, Miloslav; Zakostelska, Zuzana; Hudcovic, Tomas; Hrncir, Tomas; Stepankova, Renata; Rossmann, Pavel; Ridl, Jakub; Kostovcik, Martin; Mrazek, Jakub; Kopecny, Jan; Kobayashi, Koichi S; et al. (Inflammatory bowel diseases, 2013)
BACKGROUND: Microbial sensing by Toll-like receptors (TLR) and its negative regulation have an important role in the pathogenesis of inflammation-related cancer. In this study, we investigated the role of negative regulation of Toll-like receptors signaling and gut microbiota in the development of colitis-associated cancer in mouse model. METHODS: Colitis-associated cancer was induced by azoxymethane and dextran sodium sulfate in wild-type and in interleukin-1 receptor-associated kinase M (IRAK-M)-deficient mice with or without antibiotic (ATB) treatment. Local cytokine production was analyzed by multiplex cytokine assay or enzyme-linked immunosorbent assay, and regulatory T cells were analyzed by flow cytometry. Changes in microbiota composition during tumorigenesis were analyzed by pyrosequencing, and β-glucuronidase activity was measured in intestinal content by fluorescence assay. RESULTS: ATB treatment of wild-type mice reduced the incidence and severity of tumors. Compared with nontreated mice, ATB-treated mice had significantly lower numbers of regulatory T cells in colon, altered gut microbiota composition, and decreased β-glucuronidase activity. However, the β-glucuronidase activity was not as low as in germ-free mice. IRAK-M-deficient mice not only developed invasive tumors, but ATB-induced decrease in β-glucuronidase activity did not rescue them from severe carcinogenesis phenotype. Furthermore, IRAK-M-deficient mice had significantly increased levels of proinflammatory cytokines in the tumor tissue. CONCLUSIONS: We conclude that gut microbiota promotes tumorigenesis by increasing the exposure of gut epithelium to carcinogens and that IRAK-M-negative regulation is essential for colon cancer resistance even in conditions of altered microbiota. Therefore, gut microbiota and its metabolic activity could be potential targets for colitis-associated cancer therapy.
Keywords: RNA, Messenger; Male; metagenom; Mice, Knockout; kvantitativní polymerázová řetězová reakce; azoxymethan; regulační T-lymfocyty; western blotting; cytokiny; Colitis; signální transdukce; Interleukin-1 Receptor-Associated Kinases; Gastrointestinal Tract; kinázy asociované s receptory interleukinu-1; mužské pohlaví; toll-like receptory; polymerázová řetězová reakce s reverzní transkripcí; Real-Time Polymerase Chain Reaction; Flow Cytometry; Signal Transduction; myši knockoutované; Azoxymethane; Blotting, Western; T-Lymphocytes, Regulatory; Metagenome; Toll-Like Receptors; průtoková cytometrie; Animals; Dextran Sulfate; ženské pohlaví; Carcinogens; karcinogeny; zvířata; myši inbrední C57BL; Colonic Neoplasms; Reverse Transcriptase Polymerase Chain Reaction; gastrointestinální trakt; myši; Receptors, Interleukin-1; Mice, Inbred C57BL; nádory tračníku; receptory interleukinu-1; Cytokines; kolitida; Mice; Female; messenger RNA; síran dextranu